2004
DOI: 10.1038/sj.onc.1207398
|View full text |Cite
|
Sign up to set email alerts
|

Identification of NPM-ALK interacting proteins by tandem mass spectrometry

Abstract: Constitutive overexpression of nucleophosmin-anaplastic lymphoma kinase (NPM-ALK) is a key oncogenic event in anaplastic large-cell lymphomas with the characteristic chromosomal aberration t(2;5)(p23;q35). Proteins that interact with ALK tyrosine kinase play important roles in mediating downstream cellular signals, and are potential targets for novel therapies. Using a functional proteomic approach, we determined the identity of proteins that interact with the ALK tyrosine kinase by co-immunoprecipitation with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 56 publications
5
89
1
Order By: Relevance
“…Our group and others have described modifications of the expression of regulators of the Rho GTPases (Crockett et al, 2004;Cussac et al, 2006). We observed the extinction of the GTPase inhibitor RhoGDI2 in the proteome of an NPM-ALK( þ ) cell line, an effect shown to correlate with higher metastatic activity and poor prognosis in bladder cancers (Theodorescu et al, 2004;Cussac et al, 2006).…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…Our group and others have described modifications of the expression of regulators of the Rho GTPases (Crockett et al, 2004;Cussac et al, 2006). We observed the extinction of the GTPase inhibitor RhoGDI2 in the proteome of an NPM-ALK( þ ) cell line, an effect shown to correlate with higher metastatic activity and poor prognosis in bladder cancers (Theodorescu et al, 2004;Cussac et al, 2006).…”
Section: Introductionmentioning
confidence: 67%
“…New partners have been found that account for different functions of NPM-ALK, such as the regulation of mRNA turnover (Fawal et al, 2006). Among others, proteins regulating cell shape and cytoskeleton plasticity, two important features altered in transformed cells, were identified, leading to investigations of molecules classified as 'cytoskeleton and motility regulators' in the context of ALCLs (Crockett et al, 2004;Cussac et al, 2006). Ambrogio et al (2005) reported the association of NPM-ALK with p130Crk associated substrate (p130Cas) and described its role in actin depolymerization and transformation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the lack of any effect of the pan-Jak inhibitor on the ALK þ TCL cells (Figures 1-4) rules out the involvement of any member of this family that, beside Jak3, includes Jak1, Jak2 and Tyk2. 34 Furthermore, two SRC family inhibitors, SU6656 and PP2, used at the doses of up to 1 and 2 mM, respectively, also had no effect on the Stat3 phosphorylation and cell growth (MTT conversion assay) of the ALK þ TCL Karpas 299 cells (data not shown). This observation corroborates the previous finding that mouse embryonal fibrobast cell line devoid of three members of src family known to activate STAT3 were able to display STAT3 phosphorylation upon transfection with NPM/ALK.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins identified by MS were confirmed by Western blotting and reciprocal immunoprecipitation. 83 Proteomic-based methods for the identification and quantitation of proteins associated with the chromatin 84 or specific transcription factor complexes have been developed. Using the ICAT technique of quantitative mass spectrometry, proteins associated with a transcription factor NFE2p18/Mafk, essential for b-globin expression in murine erythroleukemia cells were determined 85 during two differentiation states.…”
Section: Differential Protein Profiling (Quantitative Proteomics)mentioning
confidence: 99%